Protective strategy of parathyroid glands during thyroid lobectomy: A retrospective cohort and case-control study. Issue 14 (9th April 2021) - Xing, Zhichao; Qiu, Yuxuan; Fei, Yuan; Xia, Baoying; Abuduwaili, Munire; Zhu, Jingqiang; Su, Anping
Abstract : Abstract: Parathyroid protection during thyroid lobectomy was not illustrated previously. Aim of this study was to find out the influence of parathyroid glands in situ preservation and autotransplantation on postoperative parathyroid function in thyroid lobectomy. Consecutive patients who underwent primary thyroid lobectomy with unilateral central neck dissection for papillary thyroid carcinoma in our center were included retrospectively. Postoperative hypoparathyroidism was defined as low parathyroid hormone (PTH) levels (<1.6 pmol/L) and keeping over 6 months was defined as permanent. Patients were divided into 3 groups: all identified parathyroid glands preserved in situ (preservation group); at least one parathyroid gland autotransplanted without accidental resection (autotransplantation group); at least one parathyroid gland accidental resected (resection group). A total of 425 patients were included. No permanent hypoparathyroidism was reported, and the rates of transient hypoparathyroidism were similar among all groups. Significantly lower serum PTH levels were found in autotransplantation group versus preservation group at postoperative 1-day (3.77 ± 1.61 vs 4.72 ± 2.31, P  < .001). Transient hypoparathyroidism was significantly associated with reduced intraoperative carbon nanoparticles utilization (57.1% vs 77.4%, P  = .039). Thyroid lobectomy was a safe surgical method for parathyroid protection no matter the practice to ipsilateral parathyroid glands. However, preservation of all parathyroid glands was still recommended considering relatively stable PTH levels.